High Voltage IGBTs and Medium Frequency Transformer in DC-DC Converters for Railway Applications - Hoffmann, Holger; Piepenbreier, Bernhard (SPEEDAM 2010, 2010)
A converter system made of series-connected converter submodules based on medium frequency (MF)-dc/dc converters can replace the conventional traction transformer that works at frequencies of 16.7 Hz or 50 Hz saving both mass and energy. Engaging multilevel topology permits the connection to the HV catenary with a line choke. MF switching performance of typical and dedicated 6.5 kV IGBTs was characterized and is given herein. The impact of chosen switching frequency and resonance frequency on transformer mass and transformer efficiency was analyzed with a coupled electromagnetic, thermal and hydraulic transformer calculation. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.highvo
Keywords: High voltage power converters; IGBT; Medium frequency transformer; Multilevel converter; Rail vehicle; Resonant converter